(untitled) (Revista de Ciências Agroveterinárias, 2009)
Animal trampling is one of the major causes of soil compaction in areas subjected to integrated croplivestock system. The objective of this work was to evaluate the effect of winter annual pasture grazing, in crop-livestock system, and other winter soil uses on soil compaction. The experiment was carried out from May 2006 to February 2007 at three sites of the North Plateau of Santa Catarina State, Brazil. Five winter treatments were investigated on each site: 1) intercropping with black oat + ryegrass + vetch + arrow leaf clover without grazing and nitrogen fertilization (multicropping cover); 2) the same intercropping, with grazing and 100 kg ha-1 of nitrogen, (grazing with N); 3) the same intercropping, with grazing and without nitrogen fertilization (grazing without N); 4) oil seed radish, without grazing and nitrogen fertilization (oil seed radish); and 5) natural vegetation, without grazing and nitrogen fertilization (fallow). Undisturbed cores were collected from the layers 2 to 7 cm and 10 to 15 cm, at three times: experiments implantation (May 2006), at maize sowing in succession of winter soil use (November 2006) and close to maize physiological maturity (February 2007). Soil total porosity, bulk density and soil resistance to penetration were evaluated in these samples. According to the environmental and management conditions, as well as the time of experimentation, the livestock presence in winter pastures, winter cover crops and fallow did not affect the variables related to soil compaction.